Photooxidation Contribution Study on the Decomposition of Azo Dyes in Aqueous Solutions by VUV-Based AOPs - Chih-Ming Ma; Gui-Bing Hong; Hua-Wei Chen; Nguyen-Thi Hang; Yung-Shuen Shen (International Journal of Photoenergy)
The effects of pH value, VUV intensity, initial dye concentration, initial H2O2 concentration, and TiO2 loading dose on the degradation of three azo dyes: acid Orange 8, acid Blue 29, and acid Blue 113 were studied to explore and compare the treatment efficiencies among the adopted AOPs. It was found that pH played an important role in the degradation of dyes using VUV irradiation. For VUV/H2O2, VUV/TiO2, and VUV/TiO2/H2O2 processes, the decoloration rates of the three azo dyes were more efficient under acidic conditions relative to alkaline conditions. The degradation rates of dyes increased with increasing concentrations of H2O2, but reaction rates were retarded at high concentrations of H2O2 because the H2O2 compound acted as a scavenger of the hydroxyl radical. In this paper, three azo dyes were decomposed efficiently by VUV irradiation only demonstrating the effectiveness of VUV direct photolysis.